Embedding risk management within new product and service development of an innovation and risk management framework and supporting risk processes, for effective risk mitigation : an action research study within the Information and Communication Technology (ICT) Sector - Joubert, Janine (Department of Information Systems, 2016)
At first glance, innovation and risk management seem like two opposing disciplines with diverse objectives. The former seeks to be flexible and encourages enhanced solutions and new ideas, while the latter can be seen as stifling such innovative thinking. Since there is a failure rate of as many as eight out of every ten products launched, it is perhaps necessary for organisations to consider applying more structured approaches to innovation, in order to better manage risks and to increase the chances of delivering improved goods and services. A risk management approach is well suited to address the challenge of failure, as it focuses not only on the negative impact of risks but also on the opportunities they present. It aligns these with the strategic objectives of the organisation to increase the chances of its success. The research objective of this study was to establish how to embed risk management within the innovation divisions of an organisation to ensure that more efficient products and services are delivered to customers. To achieve this end, action research was conducted in a large organisation operating in a high-technology environment that launches many diverse products and services and rapidly expanding service offerings to other industries. The study took four years to complete and delivered multiple interventions that successfully embedded risk management within the organisation, leading to changed behaviours and double-loop learning. Two main knowledge contributions are offered by the study. Firstly, a generic and empirically validated integrated Innovation and Risk Management Framework (IRMF) is developed and guides new product and service development by considering both best practices and risks. Secondly, a risk dashboard is designed as a design science artefact within the action research cycles, which consolidates all the knowledge that was generated during the study. This is ultimately a visual interface to support stage-gate decision making. Since the context of the study was broad, extensive and complicated, the use of mixed-method research complemented and expanded on the findings by providing another layer of support and validation. This thesis highlights the complexity of innovation and presents the need for an organising framework that will encourage innovation but is sufficiently flexible to cater for diverse needs and risks. The study delivers several other, valuable contributions regarding what, how and why incidents occur within the real-world context of new product and service development. Several generic artefacts, such as risk processes and maturity frameworks, are also developed, which can guide risk and new product and service development practitioners to deliver more efficient product and services. This study offers several novel approaches to evaluating risks and provides practical support and recommendations, addressing shortcomings of fragmented research in similar, but smaller-scale studies that have been conducted in information systems. It is the premise of this research that a much wider number of risks need to be managed as new products and services are developed, than was noted in previous studies. Effective risk management in new product and service development could lead to competitive advantage for organisations by increasing knowledge and facilitating sustainable, informed risk decision-making.